An Eulerian model for the simulation of the thermal conversion of a single large biomass particle. (15th May 2018) - Gómez, M.A.; Porteiro, J.; Chapela, S.; Míguez, J.L.
Abstract: This paper presents a comprehensive model for simulating the combustion of large biomass particles. The model implements a set of Eulerian variables that represent the components of solid biomass in a commercial CFD code. The evolution of these variables represents the thermal conversion of biomass and its interaction with the gas flow. The model consists of several reaction submodels of heat transfer and species diffusion. A wood shrinkage submodel was also proposed, and it acts locally in cells according to calculations of the consumption densities and globally in the particle according to mass and energy movements across the mesh. An experimental reactor, in which a biomass particle was irradiated with a xenon lamp, was modelled to simulate the drying and devolatilization stages under controlled conditions. Two documented experiments were simulated, and the predictions were compared with the experimental results. The temperature evolution of the particle at several depths was analysed, and a qualitative comparison of the particle shrinkage was performed. The comparison yielded reasonably good predictions for temperatures inside the particle and similar trends in log shrinkage despite some uncertainties regarding the biomass composition and experimental conditions.